Adhesive as well as preparation method and application thereof

By using the adhesive formed by positively charged and negatively charged polymer salt solutions, snail mucus is simulated, and the problems of high energy consumption and low bonding strength of existing adhesive preparation are solved, achieving high adhesion strength, extreme temperature resistance and reusable green bonding effect.

CN120505051APending Publication Date: 2025-08-19LIANGZHU LAB +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410183237.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-19
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

During the preparation process, existing adhesives have problems such as time-consuming, high energy consumption and unenvironmental by-products. Adhesives based on natural biological materials are expensive and have low bonding strength, making it difficult to achieve green environmental protection throughout the life cycle.

Method used

The viscous polymer formed by positively charged polymer salt and negatively charged polymer salt solution simulates snail mucus, and mixes it in aqueous solvent to form a coagulant layer to prepare a binder with high adhesion strength, which can be easily separated using sodium carbonate solution.

Benefits of technology

It has achieved high adhesion strength on different substrates, significantly improved shear modulus after drying, resistant to extreme temperatures, and can be reused at least 10 times without damaging the substrate. It is suitable for special fields such as aerospace and cultural relics restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120505051A_ABST
    Figure CN120505051A_ABST
Patent Text Reader

Abstract

The invention provides a green environment-friendly adhesive as well as a preparation method and application thereof, the green environment-friendly adhesive is prepared from naturally existing macromolecular polymer salt and shows high adhesion strength on different matrixes, and the adhesion effect of the green environment-friendly adhesive is far better than that of reported adhesives based on protein and natural macromolecular materials; the bonding time of the adhesive is long, and after a three-year accelerated aging test is simulated, the bonding strength is slightly attenuated; the adhesive has high-temperature resistance and low-temperature resistance, the bonded material can tolerate the extreme temperature of-150 DEG C to 200 DEG C without stripping, and in the dry extreme environments such as the dry high-temperature desert environment and the dry low-temperature space environment, the adhesive can meet the bonding requirements of materials with rough surfaces; the SFA can be separated from the surface by using an environment-friendly nontoxic alkaline sodium carbonate or sodium bicarbonate solution without damaging the surface of the base material, so that the SFA adhesive can be applied to the bonding of precious materials of the base material, such as the special fields of cultural relic repair and the like; the interface bonded by the green environment-friendly adhesive can be repeatedly used after being soaked in water, and the interface separated after soaking can be re-bonded for at least 10 times after being shifted without reducing the bonding capacity; the raw materials of the natural biopolymer are sufficient and low in price, so that the SFA has higher economic value and large-scale application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of adhesives, and in particular relates to an adhesive and a preparation method and application thereof. Background Art

[0002] Adhesives play a vital role in modern everyday applications, prompting people to develop a higher level of environmental awareness regarding their sources, ingredients, utilization, and post-use disposal, hoping for more and more alternatives to reduce carbon use. Therefore, many companies choose water-based adhesives to replace traditional solvent-based adhesives, such as polyvinyl alcohol and acrylic adhesives. However, the manufacturing process of water-based adhesives usually requires the synthesis of complex polymers, and its preparation process still cannot avoid chemical reactions, making its preparation process time-consuming and energy-intensive, and may also produce environmentally unfriendly by-products. To meet these challenges, it is hoped that high-performance adhesives that can be synthesized sustainably and efficiently from renewable resources can be developed.

[0003] The development of biomimetic adhesives that mimic the unique properties of natural adhesives is a very worthy research topic. Natural adhesives, such as those found in gecko feet or mussels, rely on unique molecular interactions that enable them to achieve strong adhesion to various substrates. By mimicking these natural adhesive systems, researchers can develop water-based adhesives that are not only environmentally friendly but also have high bonding strength and durability. For example, adhesives developed based on recombinant mussel foot protein and 3,4-dihydroxy-L-phenylalanine exhibited significant interfacial adhesion with a lap shear strength of 9.5 MPa. The coacervate formed by recombinant pentapeptides and surfactants showed a maximum strength of 16.5 MPa on a hard substrate. Although adhesives prepared based on recombinant protein coacervates have certain advantages, they are expensive and have a complex manufacturing process, making them not suitable adhesive alternatives.

[0004] Therefore, there is a need to find better raw materials for the preparation of adhesives on a relatively large scale. The mucus secreted by snails enables them to adhere to various surfaces such as rocks and trees while crawling. After drying, the shear modulus of this mucus can increase from 100Pa to 1GPa, forming a hard bond with the contact surface. Recent studies have shown that snail mucus gel contains positively charged proteins and polyanionic glycosaminoglycans. The ability of snails to adhere to various surfaces has led to the hypothesis that by mimicking the properties of snail mucus, natural materials with opposite charges may have the potential to become materials for the production of green adhesives.

[0005] However, specific adhesive development still faces difficulties: (1) Using charged recombinant proteins as adhesive raw materials is expensive, making it unrealistic to expand the scope of use; (2) Adhesives prepared from natural biomaterials reported in the past have low bonding strength; (3) Achieving green and environmentally friendly development throughout the entire life cycle, from raw material production to adhesive application and adhesive removal, remains challenging. Summary of the Invention

[0006] To address the above-mentioned issues, the present invention provides an adhesive, preparation method, and application thereof, referred to as snail-shaped adhesive (SFA). This adhesive mimics snail mucus by forming a coacervate composed of positively and negatively charged polymer salts, exhibiting high adhesion strength on various substrates. Wet SFA resembles wet snail mucus and can adapt to a variety of substrates. Upon drying, the shear modulus of SFA increases from 1700 Pa to 55 MPa, far exceeding any previously reported adhesive.

[0007] In one aspect, the present invention provides an adhesive comprising a tacky polymer formed by mixing a positively charged polymer salt solution and a negatively charged polymer salt solution.

[0008] Polymer refers to a macromolecular compound obtained by addition polymerization or condensation polymerization of monomer compounds. Monomer compounds are connected by covalent bonds and arranged regularly to form repeating units. The average number of repeating units in the polymer is called the degree of polymerization. The polymers of the present invention include high polymers and oligomers. Oligomers refer to polymers composed of fewer repeating units, including dimers, trimers, tetramers, etc., until the molecular weight reaches 10 3 And above the order of magnitude are called polymers.

[0009] In chemistry, salt refers to an ionic compound produced by the reaction of acid and base, while polymer salt refers to a compound produced by the reaction of a polymer with an acid or base. Based on the isoelectric point of its repeating unit, the polymer can be approximately regarded as an acid or base, and reacts with another acid or base (usually an inorganic substance) to produce an ionic compound polymer salt. The polymer gains or loses protons to become an ion, and forms a salt with the acid anion or alkali metal cation in the form of an ionic bond.

[0010] The viscous polymer formed by mixing the positively charged polymer salt solution and the negatively charged polymer salt solution is the effective component of the adhesive of the present invention; the adhesive mentioned in the following content refers to the effective component of the adhesive, namely the viscous polymer.

[0011] The adhesive of the present invention also contains a solvent, which is usually a green and environmentally friendly solvent, such as water; the adhesive can optionally contain one or more of a plasticizer, a filler, and an auxiliary agent according to actual needs; the plasticizer is used to increase the softness and ductility of the adhesive, and the plasticizer can be selected from titanate, epoxy resin, etc.; the filler is used to increase the hardness and strength of the adhesive, and the filler can be selected from talcum powder, quartz powder, glass fiber, etc.; the auxiliary agents include a curing agent, an antioxidant, a preservative, etc. The curing agent can help accelerate the curing and bonding of the adhesive and promote the formation of a strong bonding layer; the antioxidant can help resist oxidation and extend the service life of the adhesive; the preservative can help the adhesive resist erosion by microorganisms and chemical substances.

[0012] The adhesive of the present invention, which comprises an active ingredient, a viscous polymer, is prepared in solution from a positively charged polymer salt and a negatively charged polymer salt. The polymer salt must not be the polymer itself. Experiments conducted in the present invention have shown that preparing the adhesive polymer in a non-salt form produces only a small amount (yield less than 1%, with almost no adhesive polymer produced in the non-salt form). The adhesive polymer has lower viscosity than SFA prepared from a polymer salt and does not even possess the characteristic of significantly increasing viscosity upon drying, similar to snail mucus.

[0013] Furthermore, the polymer salt is a salt of a polymer with a degree of polymerization greater than 2.

[0014] In some embodiments, the positively charged polymer salt and the negatively charged polymer salt are water-soluble.

[0015] If the positively charged polymer salt and the negatively charged polymer salt used to prepare the adhesive of the present invention are water-soluble, a solution of the polymer salts can be prepared using water as a solvent, and the adhesive can be prepared by mixing in the water solvent. This has the following advantages: in the water solvent, the prepared adhesive can settle better and form a coacervate layer better, which is beneficial to increasing the output and enhancing the performance of the adhesive; water as a solvent is characterized by sufficient supply and low price, which is beneficial to industrial production and increased economic benefits.

[0016] Furthermore, the polymer salt is a salt of a naturally occurring polymer.

[0017] The present invention has verified that various naturally occurring polymers, when prepared in salt form, exhibit high adhesive properties in adhesives. Naturally occurring macromolecular polymers have applications in various fields, but are rarely used in adhesives. The present invention prepares naturally occurring macromolecular polymers into salts, which are then used to prepare adhesives based on their charged properties. The resulting salts have properties similar to snail mucus, and after drying, they exhibit extremely high adhesive properties, expanding the application areas of naturally occurring macromolecular polymers. Furthermore, naturally occurring macromolecular polymers, as raw materials for adhesive production, are abundant and inexpensive, facilitating industrial production and offering broad application prospects.

[0018] Furthermore, the positively charged polymer salt solution includes any one or more of a positively charged amino acid polymer salt solution, a chitosan salt solution, and a polypropylamine salt solution; the negatively charged polymer salt solution includes any one or more of a negatively charged amino acid polymer salt solution, a hyaluronate solution, a chondroitin sulfate salt solution, and a polyacrylate solution.

[0019] The above-mentioned multiple positively charged polymer salt solutions and negatively charged polymer salt solutions are combined in pairs to prepare adhesives. The resulting adhesives have similar shear modulus, lap strength, tensile strength, etc. when bonding with materials. Among them, the adhesives prepared with negatively charged amino acid polymer salt solutions and positively charged amino acid polymer salt solutions have higher bonding performance than other adhesives.

[0020] Preferably, the positively charged polymer salt solution is a positively charged amino acid polymer salt solution; and the negatively charged polymer salt solution is a negatively charged amino acid polymer salt solution.

[0021] Compared with other combinations of positively and negatively charged polymers, the adhesive prepared from positively and negatively charged amino acid polymer salts has stronger bonding properties with ceramics, and has high shear modulus, tensile strength, and lap strength.

[0022] The negatively charged amino acid polymer includes any one or more of polyglutamic acid, polyaspartic acid, polyglycine, polyalanine, and polyvaline, and when used, the salt form of the above-mentioned negatively charged amino acid polymer is taken, such as sodium salt, ammonium salt, etc.; the positively charged amino acid polymer includes any one or more of polylysine, polyarginine, and polyhistidine, and when used, the salt form of the above-mentioned positively charged amino acid polymer is taken, such as hydrochloride, phosphate, etc.

[0023] In some embodiments, the positively charged amino acid polymer salt includes any one or more salts of polylysine, polyarginine, and polyhistidine; the negatively charged amino acid polymer salt includes any one or more salts of polyglutamic acid, polyaspartic acid, polyglycine, polyalanine, and polyvaline.

[0024] Preferably, the positively charged amino acid polymer salt is a salt of polylysine; and the negatively charged amino acid polymer salt is a salt of polyglutamic acid.

[0025] More preferably, the positively charged amino acid polymer salt is ε-poly-L-lysine hydrochloride, and the negatively charged amino acid polymer salt is sodium γ-polyglutamate.

[0026] Both ε-poly-L-lysine and γ-polyglutamic acid are natural biopolymers produced through microbial fermentation. The raw materials are abundant and inexpensive, making SFA more economically valuable and having the potential for large-scale application. Moreover, the adhesive prepared from ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate has far superior bonding properties with ceramics than adhesives prepared from other amino acid polymers.

[0027] The present invention conducts extensive fundamental studies on the adhesive properties of SFA. Energy dispersive spectroscopy (EDS) is first used to characterize dried raw materials and SFA. The Cl and Na content in SFA is lower than the expected theoretical values. The significant reduction in Cl and Na content in SFA relative to ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate may be due to the selective enrichment of Cl in the SFA phase during mixing. These findings provide a possible mechanism for the formation of SFA, which may involve liquid-liquid phase separation. The formation of coacervates is primarily due to physical interactions between polymer molecules, including hydrogen bonding and electrostatic forces. These physical interactions alter the secondary structure of macromolecular polymers in solution, changing their physical properties and inducing liquid-liquid phase separation.

[0028] In some aspects, the positively charged amino acid polymer salt and / or the negatively charged amino acid polymer salt is a salt of an amino acid copolymer.

[0029] Polymers include homopolymers and copolymers. The polylysine and polyglutamic acid mentioned above are homopolymers obtained by condensation polymerization of a single amino acid monomer. The amino acid copolymers are amino acid polymers obtained by condensation polymerization of multiple amino acid monomers. During the preparation, the molar ratio of different amino acid monomers can be adjusted to specifically prepare amino acid copolymers with specific positive or negative charges and specific charges.

[0030] Furthermore, the number of positively charged amino acid monomers in the amino acid copolymer of the positively charged amino acid polymer salt is greater than the number of negatively charged amino acid monomers, and / or the number of positively charged amino acid monomers in the amino acid copolymer of the negatively charged amino acid polymer salt is less than the number of negatively charged amino acid monomers.

[0031] The limitation of the above-mentioned multiple amino acid monomers can limit the repeating units in the polymer, and a polymer salt with a specific isoelectric point can be obtained to determine whether it is positively or negatively charged. The pH conditions of production can be adjusted based on this, which can improve the performance of the adhesive while maximizing the output.

[0032] The yield of SFA often varies greatly depending on the operation, which is critical to its role as an adhesive in industrial applications. Therefore, we adjusted the pH value and feed ratio of the polymer salt solution to maximize the yield. When the two polymer salt solutions were mixed in equal weight in the pH range of 4-8, the coacervate showed the highest yield of 80%. The yield of coacervate was significantly lower than this range. In particular, in the pH range of 11 to 12, the production of coacervate was less than 20%. This may be attributed to the isoelectric point values of ε-poly-L-lysine hydrochloride units (~9.37) or γ-polysodium glutamate units (~3.6), which are both within this range. We believe that under acidic conditions, the coexisting charges of opposite polarity increase the possibility of molecular entanglement to form an electrocomplex, and the large number of charges with opposite polarity promotes this process.

[0033] Furthermore, the pH of the positively charged polymer salt solution and the negatively charged polymer salt solution is 2-10.

[0034] Preferably, the pH of the positively charged polymer salt solution and the negatively charged polymer salt solution is 4-8.

[0035] More preferably, the pH of the positively charged polymer salt solution and the negatively charged polymer salt solution is 7.

[0036] pH not only affects the yield of sticky polymer formation, but also affects the microscopic molecular arrangement of the sticky polymer, thereby affecting the stability and bonding properties of the adhesive. Experiments show that the adhesive prepared at a pH of 7 has the best bonding properties.

[0037] Furthermore, the charge ratio of the positively charged polymer salt solution to the negatively charged polymer salt solution is 1:0.2 to 1:5.

[0038] Preferably, the charge ratio of the positively charged polymer salt solution to the negatively charged polymer salt solution is 1:1.

[0039] SFA, similar to snail mucus, exhibits viscous yet plastically deformable properties. While maintaining the same feed ratio that yielded the highest SFA yield, variations in polymer salt feed concentration resulted in varying viscosities and adhesive abilities. Increasing the concentration from 5% to 20% resulted in a slight change in the water content of the SFA, from 62% to 64%. However, the complex viscosity (η) of the SFA decreased dramatically, from 5% (337.9 Pa·s) to 20% (7.7 Pa·s), a nearly 44-fold decrease.

[0040] In addition, under constant stress, the loss modulus (G") and storage modulus (G') of SFA with different concentrations showed similar trends. After the evaporation-induced dehydration process, the SFA-bonded glass slides were subjected to lap shear testing. Consistent with G', G", and η, the SFA formed at 5% had the strongest bonding strength (~4.08 MPa), far exceeding that of the SFA formed at 20% on glass (1.57 MPa).

[0041] The mechanism behind this phenomenon is that increasing material concentration compromises the molecular interactions between ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate due to increased steric hindrance, thereby reducing structural changes such as orientation or alignment between the polymer molecules and altering the viscoelastic behavior of the coacervate. During dehydration, the coacervate is further compressed into tightly entangled aggregates. The differential evolution of the secondary structure within the coacervate may influence the overall mechanical properties of the resulting aggregates, impacting their adhesion.

[0042] Furthermore, the concentration of the positively charged polymer salt solution and the negatively charged polymer salt solution is 5-20%.

[0043] Preferably, the concentration of the positively charged polymer salt solution and the negatively charged polymer salt solution is 5%.

[0044] In the field of hydrogels, hydrogels are often prepared using extremely low concentrations of positively charged polyamino acids and negatively charged polyamino acids, such as a concentration of 0.05%. At this concentration, molecular interactions between polyamino acids are difficult to fully occur, and no structural changes such as the arrangement of macromolecular polymers occur. The secondary structure of the macromolecular polymers does not change. In addition, the raw materials used to prepare the hydrogel are different from those of the present invention. They are polyamino acids, not salts, and therefore do not have the properties of a snail-type adhesive.

[0045] The raw material concentration used in the present invention is much higher than the concentration used in hydrogel preparation, and an unexpected effect is achieved by increasing the concentration, realizing an effect similar to snail mucus. However, the higher the concentration, the better. When the concentration is increased, the adhesion performance decreases significantly. Therefore, preparation at a concentration of 5% is a necessary condition for achieving the best adhesion effect, which is also a major discovery of the present invention that breaks the prejudice of the prior art.

[0046] In another aspect, the present invention provides a method for preparing an adhesive, comprising the following steps:

[0047] (1) Using a neutral buffer as a solvent, a positively charged polymer salt solution and a negatively charged polymer salt solution are prepared respectively;

[0048] (2) The positively charged polymer salt solution and the negatively charged polymer salt solution are mixed and settled;

[0049] (3) Separate the lower coacervate layer.

[0050] The neutral buffer solution is used as a solvent to control the pH value during the preparation process to be around 7, thereby promoting the formation of a coacervate layer, increasing the yield, and improving the adhesive properties of the prepared adhesive.

[0051] The separation of the coacervate layer in step (3) can be carried out by various methods, such as absorption in some small-scale tests in the embodiments of the present invention. However, in actual production, large-scale production can adopt centrifugation, filtration, etc. These methods are all methods for separating the coacervate layer and therefore fall within the scope of protection of the present invention.

[0052] Furthermore, step (3) is: centrifugation to separate the lower coacervate layer.

[0053] On the other hand, the present invention provides a method for reusing an adhesive, wherein after using the adhesive to bond test pieces, the test pieces are immersed in water to separate them, and then they can be bonded again.

[0054] Soaking SFA in water for a long time can separate it, but it can be re-bonded later; using sodium carbonate solution can quickly and completely remove the adhesive, but re-bonding is not possible.

[0055] The present invention subjected the SFA-bonded ceramic to 10 fracture-cure cycles, with load testing performed at each cycle. Lap shear tests recorded after each cycle showed that repeated use of the SFA did not reduce its bond strength. This feature highlights its significant recyclability, surpassing traditional solvent-based adhesives and significantly helping to reduce material consumption. Furthermore, the non-covalent nature of the coacervate gives the SFA additional properties, allowing for easier material separation and recycling after application.

[0056] In another aspect, the present invention provides a use of a mixture for preparing a reusable adhesive having improved bonding strength to a rough medium surface, wherein the mixture comprises a positively charged polymer salt solution and a negatively charged polymer salt solution.

[0057] In some embodiments, the rough media surface comprises a ceramic surface.

[0058] Ceramics have high surface roughness, and existing adhesives are difficult to provide high bonding strength for bonding ceramics. Therefore, there has always been a huge technical gap in bonding ceramics. The adhesive provided by the present invention has extremely high bonding strength to ceramics, which is far higher than any existing reported adhesive. The adhesive of the present invention fills the technical gap in the field of bonding ceramics.

[0059] To investigate why SFA exhibits the highest adhesion on ceramic surfaces, we used atomic force microscopy (AFM) to observe the surface potential and roughness of different materials. There were no significant differences in surface potential between these materials. However, the average roughness (Ra) of ceramics was 283.3 nm, four times that of wood (~58.3 nm) and fifty to one hundred times that of glass (~2.9 nm) and steel (~4.1 nm). Considering the interface between the dried adhesive and the material surface, where the SFA seamlessly integrates along the contours to form a dense colloidal layer, it is reasonable that SFA adheres better to materials with greater roughness. Due to the greater surface area of the rough surface, there are more interaction sites per unit volume between the SFA and the rough material. Therefore, a complementary mechanism of mechanical interlocking, beyond hydrogen bonding, occurs at the molecular level between the SFA and the rough surface. This synergistic effect significantly enhances the bond strength. Scanning electron microscopy (SEM) observations of the dried material on the ceramic surface show that the SFA forms a dense colloidal layer on the ceramic surface after drying, demonstrating strong interconnectivity.

[0060] The above mechanism reveals the reason why the adhesive of the present invention has high bonding performance for bonding ceramics. It also reveals that the adhesive of the present invention is not limited to bonding ceramics, but has higher bonding performance with materials with rough surfaces. The adhesives currently reported all have higher bonding performance on materials with smooth surfaces. In practice, the viscosity of existing adhesives on steel surfaces is significantly higher than that of SFA, but the bonding performance of SFA on glass and wood surfaces is slightly higher than that of other adhesives, and the viscosity of SFA on ceramic surfaces is significantly higher than that of other adhesives.

[0061] Based on the above test results and the bonding principle, it can be inferred that SFA is a superior choice to any existing adhesive for bonding other materials with high surface roughness. Therefore, SFA complements the shortcomings of existing adhesives.

[0062] This study designed a snail-like adhesive (SFA) by modulating the electrostatic interactions and molecular entanglement of two polymer salts. This adhesive mimics snail mucus by forming a coacervate using the polymers, exhibiting high adhesion strength on diverse substrates. Wet SFA resembles wet snail mucus and can adapt to a wide range of substrate types. Upon drying, the shear modulus of SFA increases from 1700 Pa to 55 MPa, forming a hard lock between the contacting surface and within the coacervate. We demonstrated that the adhesive exhibits high bond strength (~28 MPa) on rough surfaces, a record for reported bio-based adhesives. Even after three years of accelerated aging testing at ambient temperature, the bond strength of substrates bonded with SFA showed minimal degradation. Furthermore, SFA can withstand extreme temperatures ranging from -150°C to 300°C, sufficient for use in aerospace adhesives. Sodium carbonate solution can be used to gently detach the SFA from surfaces, thereby preventing consumer products from accumulating in landfills at the end of their useful life. A simple hydration process also allows the SFA to be reshaped, reformed, and recycled at least 10 times without degrading its adhesive ability. Compared to existing water-based adhesives, our snail-inspired adhesive is sustainable throughout its entire product lifecycle, from production to removal, and exhibits superior, long-lasting adhesion to a variety of materials. This bio-based adhesive has the potential to replace traditional adhesives and provide a more sustainable option for everyday or specialized applications such as cultural relic restoration and aerospace adhesives.

[0063] The extraordinary adhesive properties of SFA make it a valuable asset in all aspects of daily life. Compared with previously reported bio-based and synthetic water-based adhesives, SFA exhibits very strong adhesive properties. When SFA effectively adhered three ceramic sheets with an overlap of 3 cm, 2 , was able to support a 75 kg adult in a shear test under tension. Even when the overlap area was halved in a tensile test, SFA demonstrated excellent load-bearing capacity. In addition to its wide range of applications, SFA is particularly useful in professional settings, such as the restoration of archaeological artifacts. The strong adhesion of SFA on ceramics makes it suitable for repairing ceramic artifacts. Notably, the adhesion ability of SFA is not limited to porcelain, but also includes materials such as cattle bones, which have many micropores. For example, in an adhesion test, a broken cattle femur sealed with SFA remained intact when a 20 kg bucket of water was lifted. This shows that SFA has the potential to play a role in a wide range of applications, especially in establishing strong adhesion between objects with rough surfaces.

[0064] In addition, as a green adhesive, SFA does not involve any organic solvents in its production, use and removal processes, thus achieving non-toxic and pollution-free throughout its entire life cycle.

[0065] The present invention has the following beneficial effects:

[0066] 1. The adhesive provided by the present invention exhibits high adhesion strength on different substrates, with a record bonding strength of 28 MPa on irregular or rough surfaces. After drying, the shear modulus increases from 1700 Pa to 55 MPa, far exceeding the bonding effect of previously reported adhesives.

[0067] 2. The adhesive provided by the present invention exhibited minimal attenuation in bond strength after undergoing a simulated three-year accelerated aging test at extreme ambient temperatures. The adhesive can also withstand extreme temperatures ranging from -150°C to 300°C, demonstrating its high stability and resistance to aging or thermal decomposition, making it suitable for use as an aerospace adhesive.

[0068] 3. Sodium carbonate solution can be used to gently separate SFA from the surface without damaging the substrate surface. Its complete separation effect is conducive to the application of SFA in special fields such as cultural relics restoration;

[0069] 4. The adhesive provided by the present invention can be reshaped and recycled at least 10 times without reducing its adhesive ability, and can be reused to improve economic benefits;

[0070] 5. The adhesive provided by the present invention preferably uses ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate as building blocks to physically cross-link the coacervate. ε-poly-L-lysine and γ-polyglutamic acid are both natural biopolymers produced by microbial fermentation. The raw materials are abundant and inexpensive, making SFA more economically valuable and potentially applicable on a large scale.

[0071] Detailed description

[0072] The present invention provides an adhesive, a preparation method and application thereof. The preparation involves polymers, polymer salts, amino acid polymer salts, charged amino acids, etc. The prepared adhesive has properties similar to snail mucus, and the adhesive performance is improved by 4 orders of magnitude after drying, and has broad application prospects.

[0073] polymer

[0074] Polymers, also known as high molecular weight compounds, generally refer to compounds with relative molecular masses ranging from thousands to millions (order of magnitude), but also include oligomers with lower relative molecular masses; the vast majority of high molecular weight compounds are mixtures of many homologues with different relative molecular masses, so the relative molecular mass of a polymer is the average relative molecular weight.

[0075] Compounds with relative molecular mass ranging from thousands to millions (order of magnitude) are called polymers. In addition, polymers also include oligomers, which are polymers composed of fewer repeating units, including dimers, trimers, tetramers, etc., until the molecular weight reaches 10 3And above orders of magnitude are called polymers; the smallest molecular weight is a dimer, which chemically refers to a new substance formed by the combination of two molecules. It can be two identical molecules or two different molecules, and conceptually they all belong to polymers.

[0076] Monomer compounds are linked by covalent bonds and arranged regularly to form repeating units. The average number of repeating units in the polymer is called the degree of polymerization; the degree of polymerization of the polymer of the present invention is greater than 2.

[0077] Polymers are composed of thousands of atoms linked together by covalent bonds. Although they have a large molecular weight, they are linked together in simple, repeating structural units. Polymers are virtually non-volatile and exist in solid or liquid form at room temperature.

[0078] Solid polymers can be divided into crystalline and amorphous states based on their structural form. The former has regular, orderly molecular arrangement, while the latter has irregular molecular arrangement. The same polymer compound can exhibit both crystalline and amorphous structures. Most synthetic resins have an amorphous structure. The atoms that make up a polymer chain are held together by covalent bonds, and polymer chains generally have two different shapes: chain-like and bulk-like.

[0079] A large number of high-molecular-weight compounds used as materials in the world today are made by polymerizing low-molecular-weight organic compounds using coal, petroleum, natural gas, and other raw materials. These low-molecular-weight compounds are called "monomers," and the high-molecular-weight compounds produced by their polymerization are called polymers.

[0080] There are also a large number of naturally occurring materials that are polymers, such as carbohydrates and proteins. Polysaccharides are polymers composed of monosaccharides as monomers, and proteins are polymers obtained by spatially polymerizing and arranging multiple polypeptides composed of complex sequences of amino acids. A variety of naturally occurring polymers, such as chitosan and γ-polyglutamic acid, can be used as raw materials for the adhesive of the present invention in the form of salts.

[0081] Polymers include homopolymers and copolymers. Homopolymers are polymers made from only one monomer, while copolymers are polymers made from different monomers. The adhesive raw materials of the present invention can be homopolymers or copolymers. Homopolymers are exemplified by polylysine, while copolymers are polymers made from multiple different amino acids.

[0082] Isoelectric point

[0083] The isoelectric point is the pH value at which a molecule does not migrate in an electric field (the net charge of the molecule is zero), even if the molecule is in the zwitterionic state.

[0084] The isoelectric point refers to charged substances and is not limited to amphoteric electrolytes such as amino acids and proteins. Proteins are, of course, amphoteric electrolytes, and their isoelectric point is related to the ratio of acidic to basic amino acids they contain. Different proteins have different isoelectric points depending on their amino acid residue composition. When a solution is at a specific pH, the positive and negative charges on a protein are exactly equal, and in an electric field, the protein will neither migrate toward the anode nor toward the cathode. Therefore, electrophoresis can be used to determine the isoelectric point of a protein and to separate and purify protein molecules of varying charge, size, and shape. At their isoelectric point, proteins are most unstable and have minimal solubility because they lack the mutual repulsion caused by like charges. They readily aggregate into larger aggregates through electrostatic attraction, resulting in precipitation. At the same time, the protein's viscosity, osmotic pressure, swelling capacity, and electrical conductivity are all minimized.

[0085] Amino acids exhibit typical reactions involving amino and carboxyl groups. For example, amino groups can undergo hydroxylation and acylation, reacting with nitrous acid; carboxyl groups can form esters, acyl chlorides, or amides. Furthermore, the presence of both amino and carboxyl groups in the molecule gives amino acids unique properties. Amino acids contain both amino and carboxyl groups, allowing them to form salts with strong acids and bases. Amino acids are amphoteric substances and can form internal salts.

[0086] The high melting point (actually the decomposition point) and insolubility in nonpolar organic solvents of amino acids indicate that they exist as zwitterions in their crystalline state. In aqueous solution, amino acid dipole ions can either combine with an H+ to form a positive ion or lose an H+ to become a negative ion. These three ions coexist in aqueous solution by converting between gaining and losing H+, and the solution is in equilibrium when the pH reaches the isoelectric point.

[0087] The isoelectric point is not a neutral point. Different amino acids have different isoelectric points due to their different structures. The isoelectric point of an acidic amino acid aqueous solution is necessarily less than 7, so more base must be added to equalize the amount of positive and negative ions. Conversely, an alkaline amino acid aqueous solution contains more negative ions, so acid must be added to increase the amount of positive ions. Therefore, the isoelectric point of alkaline amino acids is necessarily greater than 7.

[0088] The amino acid polymers involved in the present invention, whether homopolymers, copolymers, oligomers or polymers, are derived from the polymerization of amino acids and have isoelectric points similar to those of the above-mentioned proteins.

[0089] Salt

[0090] In chemistry, salt refers to a type of compound composed of metal ions or ammonium ions (NH4+) and acid ions or non-metal ions, or an ionic compound. Generally speaking, salt is the product of a double decomposition reaction, such as sulfuric acid and sodium hydroxide producing sodium sulfate and water. There are also other reactions that can produce salts, such as displacement reactions.

[0091] Salts are divided into simple salts and complex salts. Simple salts are divided into normal salts, acid salts, and basic salts, while complex salts are divided into double salts and dissociation salts. Acid salts contain hydrogen ions in addition to metal ions and acid radical ions, while basic salts contain hydroxide ions in addition to metal ions and acid radical ions. When double salts are dissolved in water, they can form complex salts with the same ions as the original salt; when dissociation salts are dissolved in water, they can form complex salts with different complex ions from the original salt.

[0092] Many ionic compounds are soluble in water or similar solvents. The solubility of a compound is related to the constituent anions and cations, as well as the solvent, and therefore has a specific relationship. Among cations, all salts of sodium, potassium, and ammonium ions are soluble in water; among anions, salts of nitrate and bicarbonate ions are soluble in water. With the exception of barium sulfate, calcium sulfate, and lead sulfate, most sulfate salts are also soluble in water. Halogen salts (chlorine, bromine, and iodine) are insoluble, as are mercury, copper, silver, thallium, and lead. However, if the bonds between ions are strong, forming a highly stable solid, they will not dissolve easily in water. For example, most carbonates are insoluble in water.

[0093] Generally, salts are classified as inorganic compounds, but there are also salts of some organic compounds, such as salts of organic acids. Among them, the more important ones are carboxylates, such as acetate CH3COO - and sodium ions Na + Sodium acetate and copper ions Cu 2+ This forms copper acetate. Acetic acid has only one COOH group, carrying a valence of -1, while citric acid has three COOH groups, carrying a valence of -3. The salts formed include sodium citrate and calcium citrate. The anions and cations of acetate and citrate salts are ionically bonded, unlike the covalent bonds of common organic compounds, hence the name "salts." Carboxylates, which also include fatty acid salts, are the most commonly used of these salts. For example, soap is a mixture of sodium and potassium fatty acids of varying molecular weights. Salts of these long-chain fatty acids lack a crystalline structure.

[0094] polymer salts

[0095] In chemistry, salt refers to an ionic compound produced by the reaction of acid and base, while polymer salt refers to a compound produced by the reaction of a polymer with an acid or base. Based on the isoelectric point of its repeating unit, the polymer can be approximately regarded as an acid or base, and reacts with another acid or base (usually an inorganic substance) to produce an ionic compound polymer salt. The polymer gains or loses protons to become an ion, and forms a salt with the acid anion or alkali metal cation in the form of an ionic bond.

[0096] Some units of water-soluble polymers have an isoelectric point other than 7 in aqueous solution, and therefore have an electric charge in aqueous solution and can react with an acid or a base to form a polymer salt.

[0097] A positively charged polymer is a polymer that can combine with an acid molecule to produce a salt, for example, it combines with hydrochloric acid to form a hydrochloride, in which case the polymer is positively charged and the chloride ion is negatively charged; a negatively charged polymer is a polymer that can combine with an alkali molecule to produce a salt, for example, it combines with sodium hydroxide to form a sodium salt, in which case the polymer is negatively charged and the sodium ion is positively charged.

[0098] Charged amino acids

[0099] The R group (side chain group) of an amino acid determines the type and properties of the amino acid. Among the 20 basic amino acids, some have positively charged R groups, and these are called basic amino acids; others have negatively charged R groups, and these are called acidic amino acids.

[0100] Among the basic amino acids, there are three basic amino acids, namely lysine, arginine and histidine. The isoelectric points of these amino acids are greater than 7, so they carry a positive charge in aqueous solution; the acidic amino acids are glutamic acid, aspartic acid, glycine, alanine and valine. The isoelectric points of these amino acids are less than 7, so they carry a negative charge in aqueous solution.

[0101] Amino acid polymer salt

[0102] Amino acid polymers are polymers obtained by condensation polymerization of amino acids as monomers. Amino acid monomers have amino groups and carboxyl groups. Therefore, the amino acid polymer contains an amino group and a carboxyl group that have not undergone condensation reaction, respectively at the two ends of the long chain of the amino acid polymer.

[0103] In addition, amino acid polymers can also be synthesized through biological pathways. The molecular structure of amino acid polymers synthesized by biological pathways is different from that of artificially synthesized amino acid polymers. Biological pathways often include bacterial synthesis, etc. Such amino acid polymers exist naturally and have been applied in many fields.

[0104] Amino acid polymers can react with acids or bases to obtain amino acid polymer salts; amino groups can combine with acid molecules, such as combining with a molecule of hydrogen chloride to form hydrochloride, at which time the polymer is positively charged and the chloride ion is negatively charged; carboxyl groups can combine with base molecules to form metal salts or ammonium salts, such as sodium salts, at which time the polymer is negatively charged and the sodium ion is positively charged. BRIEF DESCRIPTION OF THE DRAWINGS

[0105] Figure 1 :SFA yield statistics at various charge ratios

[0106] Figure 2 : SFA yield at each pH value

[0107] Figure 3 :Complex viscosity and water content of SFA at different mixing concentrations (polymer aqueous solution concentrations)

[0108] Figure 4 :Loss modulus (G") and storage modulus (G') of SFA with different concentrations

[0109] Figure 5 :SEM images of ε-poly-L-lysine hydrochloride, sodium γ-polyglutamate, and SFA dried on equal amounts of ceramic

[0110] Figure 6 :SEM image of dense colloidal layer of SFA on ceramic surface

[0111] Figure 7 :Energy dispersive spectroscopy (EDS) of dried raw materials and SFA

[0112] Figure 8 :Element distribution statistics of ε-poly-L-lysine hydrochloride, γ-polyglutamate sodium and their coacervates

[0113] Figure 9 : Optical microscope image of SFA

[0114] Figure 10 Snail-type adhesive can generate huge hydrogen bonding force, especially on the rough surface of materials, which can produce mechanical interlocking effect.

[0115] Figure 11 : Circular dichroism of coacervates, ε-poly-L-lysine hydrochloride, and sodium γ-polyglutamate

[0116] Figure 12 : Percentage of secondary structure in coacervates, ε-poly-L-lysine hydrochloride, and γ-polyglutamate

[0117] Figure 13 : CD spectrum of the coacervate

[0118] Figure 14 :XPS full spectrum of ε-poly-L-lysine hydrochloride, γ-polyglutamate sodium and coacervate

[0119] Figure 15 :N1s spectra of ε-poly-L-lysine hydrochloride, γ-polyglutamate sodium and coacervate

[0120] Figure 16 :C1s spectra of ε-poly-L-lysine hydrochloride, γ-polyglutamate sodium and coacervate

[0121] Figure 17 Comparison of SFA with reported bio-based and water-based synthetic adhesives for bonding ceramics, glass, wood, and steel

[0122] Figure 18 : Load-displacement curves of SFA at different time points (0, 15, 30, 45, 60, 75 days) in the accelerated aging test

[0123] Figure 19 : Lap strength of SFA at different time points (0, 15, 30, 45, 60, 75 days) in the accelerated aging test

[0124] Figure 20 :Load-displacement curves of SFA after heating at different temperatures (25, 100, 200, 300, 400℃) for 30 minutes

[0125] Figure 21 :Shear strength of SFA after heating at different temperatures (25, 100, 200, 300, 400℃) for 30 minutes

[0126] Figure 22 :Dynamic Mechanical Analysis (DMA) of SFA Adhesion at Low Temperature

[0127] Figure 23 :Cold temperature tolerance of SFA

[0128] Figure 24 : Load-displacement curves of 10 fracture-curing cycles of SFA and ceramic bonding

[0129] Figure 25 : Clean the slides containing adhesive with deionized water and sodium carbonate solution

[0130] Figure 26 :SFA carries 75kg adult

[0131] Figure 27 : SFA sealed broken bovine femur remains intact DETAILED DESCRIPTION

[0132] The present invention will be further described in detail below with reference to the accompanying drawings and examples. It should be noted that the following examples are intended to facilitate understanding of the present invention and do not have any limiting effect on the present invention.

[0133] Example 1

[0134] Chitosan hydrochloride solution and sodium hyaluronate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; after thorough mixing and a sedimentation period of 30 seconds, the mixture was centrifuged at 1300 rpm for 10 minutes to separate it into two different phases, the lower layer consisting of a coacervate layer, referred to as snail-type adhesive (SFA), and the obtained SFA was obtained using a 1 mL syringe.

[0135] Example 2

[0136] Chitosan hydrochloride solution and sodium chondroitin sulfate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; other conditions were the same as in Example 1.

[0137] Example 3

[0138] The chitosan hydrochloride solution and the sodium polyacrylate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0139] Example 4

[0140] The chitosan hydrochloride solution and the sodium polyglutamate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0141] Example 5

[0142] The polypropylamine hydrochloride solution and the sodium hyaluronate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0143] Example 6

[0144] The polypropylamine hydrochloride solution and the sodium chondroitin sulfate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0145] Example 7

[0146] The polypropylamine hydrochloride solution and the sodium polyacrylate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0147] Example 8

[0148] The polypropylamine hydrochloride solution and the sodium gamma-polyglutamate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as those in Example 1.

[0149] Example 9

[0150] The ε-poly-L-lysine hydrochloride solution and the sodium hyaluronate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; other conditions were the same as in Example 1.

[0151] Example 10

[0152] The ε-poly-L-lysine hydrochloride solution and the sodium chondroitin sulfate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; other conditions were the same as in Example 1.

[0153] Example 11

[0154] The ε-poly-L-lysine hydrochloride solution and the sodium polyacrylate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; other conditions were the same as in Example 1.

[0155] Example 12

[0156] The ε-poly-L-lysine hydrochloride solution and the γ-polyglutamate sodium solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0157] The source of ε-poly-L-lysine hydrochloride is Yiyang Biotechnology Co., Ltd.; the source of γ-polyglutamate sodium is Huaxi Biotechnology Co., Ltd.

[0158] Example 13: Lap shear test of adhesive

[0159] The wet snail-type adhesive (SFA) prepared above was applied to the surface of the object to be bonded via a syringe and then allowed to dry naturally at room temperature for three days. The objects bonded with the wet SFA and the dried SFA were then tested. Lap shear and tensile tests were conducted according to ASTM F2255-05 and F2258-05, respectively. All tests were performed using an Instron 5943 at a rate of 1 mm / min.

[0160] In the lap shear test, the bonding area of alumina ceramic is 0.25 cm 2 ,, the bonding area of the glass is also 1.25cm 2 , the bonding area of steel is 2.5cm 2 In the tension test, the bonding area between glass and steel was 1.25cm 2 , the bonding area of alumina ceramics is 0.5cm2 The tensile strength is calculated using the F / A formula, where F is the maximum load and A is the bond area.

[0161] Shear modulus is the ratio of shear stress to shear strain within the proportional limit of elastic deformation under shear stress. It characterizes a material's ability to resist shear strain. In the lap shear test of adhesives in the examples, a higher shear modulus indicates that the adhesive requires more shear stress to resist unit strain, indicating higher bonding performance.

[0162] The maximum load reflects the maximum load required to maintain adhesion between the adhesive and the material. Due to the different bonding areas between the materials, the maximum load is usually divided by the bonding area to obtain the tensile strength. The higher the tensile strength, the higher the bonding performance of the adhesive material.

[0163] The shear modulus of the adhesives prepared in Examples 1 to 12 with ceramics before and after drying is shown in Table 1, the shear modulus with glass is shown in Table 2, the shear modulus with steel is shown in Table 3, and the tensile strength with ceramics is shown in Table 4.

[0164] Table 1: Shear modulus of adhesives with different compositions before and after drying and ceramics

[0165]

[0166] Table 2: Shear modulus of adhesives with different compositions before and after drying on glass

[0167]

[0168] Table 3: Shear modulus of adhesives with different compositions before and after drying and steel

[0169]

[0170] Table 4: Tensile strength of adhesives with different compositions before and after drying and ceramics

[0171]

[0172]

[0173] According to the above test results, Examples 1 to 12 used negatively charged polymer salt solutions and positively charged polymer salt solutions to prepare the adhesives of the present invention. The prepared adhesives of various components all had properties similar to snail mucus. After drying, the shear modulus between the adhesive and the material increased by four orders of magnitude. The maximum load, tensile strength, and shear modulus showed the same trend, with an increase of four orders of magnitude before and after drying, demonstrating that the adhesive properties of the adhesive were significantly improved after drying.

[0174] The snail-shaped adhesive prepared above has different bonding properties when applied to surfaces of different materials. The bonding performance is the highest with ceramics, lower with steel, and lower than with glass. This is related to the surface properties of the materials and will be studied in detail in subsequent examples.

[0175] Examples 1 to 12 cover adhesives prepared from a combination of various ingredients. Generally speaking, the adhesive properties of these adhesives are not very different, and all achieve very high shear modulus, maximum load and tensile strength after drying, especially when bonding with ceramics; however, the present invention discovered that one of the adhesives has outstanding adhesive properties, namely, an adhesive prepared from a positively charged amino acid polymer salt solution and a negatively charged amino acid polymer salt solution.

[0176] Example 14: Comparative Test of Polymer and Polymer Salt

[0177] According to the test results of Example 13, positively charged polymer salts and negatively charged polymer salts can produce a coacervate in an aqueous solvent. The coacervate is a viscous polymer and is an effective component of the adhesive of the present invention. This example uses a positively charged polymer and a negatively charged polymer, mixed in an aqueous solvent, to try whether the polymer in a non-salt form can be used to prepare an adhesive.

[0178] The first step is to prepare an aqueous solution of the polymer. This step is hindered by the fact that most polymers have low solubility in water compared to polymer salts, and adhesives cannot be prepared at low concentrations. In this example, two water-soluble polymers, ε-poly-L-lysine and γ-polyglutamic acid, were selected and mixed in a mass ratio of 1:1 at pH 7 with a concentration of 5%. After thorough mixing and a 30-second sedimentation period, the mixture was centrifuged at 1300 rpm for 10 minutes to separate it into two different phases. The lower layer consisted of a coacervate layer, referred to as a snail-type adhesive (SFA). The obtained SFA was obtained using a 1 mL syringe.

[0179] First, the yields of SFA prepared from the polymer of this example and the SFA prepared in Example 12 were compared. The yield was calculated by dividing the mass of the coacervate after complete drying by the dry weight of the feed. The yield of Example 12 was approximately 80%, while the yield of this example was only 0.6%. The mixing of polymers in non-salt form produced almost no sticky polymer.

[0180] Next, the bonding properties of the SFA prepared from the polymer of this example were compared with those of the SFA prepared in Example 12. The shear modulus of bonding between the SFA and ceramic was tested according to the method of Example 13. The results are shown in Table 5.

[0181] Table 5: Shear modulus of adhesives with different compositions before and after drying and ceramics

[0182]

[0183] According to the test results, SFA prepared from polymers not only has an extremely low yield, but also has far inferior bonding strength to SFA prepared from polymer salts. The shear modulus of SFA prepared from polymers in bonding ceramics is 4 orders of magnitude lower than that of SFA prepared from polymer salts. The shear modulus before and after drying only increases by less than 4 times. It can be considered that it does not have properties similar to snail mucus.

[0184] Therefore, the polymer is not only ineffective for preparing SFA (yield is less than 1%), but the resulting coacervate has low viscosity both in wet and dry conditions and does not possess the properties of snail mucus.

[0185] In principle, polymers are weakly ionized in aqueous solution and exist primarily as intact molecules. Therefore, positively and negatively charged polymers cannot adsorb to each other at the microscopic level and complete physical processes such as molecular entanglement and alignment. However, polymer salts, in aqueous solution, fully expose their polymer units as charged ions. This allows the charged polymer ions to complete physical processes such as adsorption and molecular entanglement, ultimately settling to form a coacervate layer and producing a sticky polymer. Therefore, only polymer salts can be used to prepare the adhesives of the present invention.

[0186] Example 15

[0187] The polyarginine hydrochloride solution and the sodium gamma-polyglutamate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0188] Example 16

[0189] The polyhistidine hydrochloride solution and the sodium gamma-polyglutamate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0190] Example 17

[0191] The ε-poly-L-lysine hydrochloride solution and the sodium polyaspartate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0192] Example 18

[0193] The polyarginine hydrochloride solution and the sodium polyaspartate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0194] Example 19

[0195] The polyhistidine hydrochloride solution and the sodium polyaspartate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0196] Example 20

[0197] The ε-poly-L-lysine hydrochloride solution and the sodium polyglycinate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0198] Example 21

[0199] The polyarginine hydrochloride solution and the sodium polyglycinate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0200] Example 22

[0201] The polyhistidine hydrochloride solution and the sodium polyglycinate solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0202] Example 23

[0203] The ε-poly-L-lysine hydrochloride solution and the sodium polyalanine solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0204] Example 24

[0205] The polyarginine hydrochloride solution and the polyalanine sodium solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0206] Example 25

[0207] The polyhistidine hydrochloride solution and the polyalanine sodium solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0208] Example 26

[0209] The ε-poly-L-lysine hydrochloride solution and the sodium polyvaline solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other conditions were the same as in Example 1.

[0210] Example 27

[0211] The polyarginine hydrochloride solution and the polyvaline sodium solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0212] Example 28

[0213] The polyhistidine hydrochloride solution and the polyvaline sodium solution were mixed at a charge ratio of 1:1 at pH 7 to obtain a mixture with a concentration of 5%; the other steps were the same as in Example 1.

[0214] Example 29: Adhesive Properties of Polyamino Acid Adhesives

[0215] According to Example 13, compared with adhesives prepared from other charged polymer salt solutions, the adhesives prepared from the positively charged amino acid polymer salt solution and the negatively charged amino acid polymer salt solution exhibited better bonding properties with various materials.

[0216] Examples 12 and 15 to 28 are preparation examples of adhesives prepared from various positively charged amino acid polymer salt solutions and negatively charged amino acid polymer salt solutions. The ceramic shear modulus of these adhesives was tested according to the method of Example 1, and the results are shown in Table 6.

[0217] Table 6: Shear modulus of adhesives with different compositions before and after drying and ceramics

[0218]

[0219] According to test results, the negatively charged amino acid polymer salt can be selected from the group consisting of polyglutamate, polyaspartate, polyglycine, polyalanine, and polyvaline; the positively charged amino acid polymer salt can be selected from the group consisting of polylysine, polyarginine, and polyhistidine. Adhesives prepared from these positively and negatively charged amino acid polymer salts exhibited excellent adhesive properties, with the shear modulus increasing by four orders of magnitude after drying. Adhesives prepared from ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate exhibited the best performance.

[0220] Example 30: Optimization of pH and charge ratio in adhesive preparation

[0221] The yield of SFA often varies greatly from operation to operation, which is crucial for its role as an adhesive in industrial applications.

[0222] According to Example 29, the present invention confirms that the adhesive prepared by ε-poly-L-lysine hydrochloride and γ-polyglutamate has the best performance. Therefore, this example selects the above-mentioned ε-poly-L-lysine hydrochloride and γ-polyglutamate as raw materials, and adjusts the charge ratio of their mixture. Because the average molecular weight of the amino acid polymers is similar, the charge ratio of the polymer salt can be determined based on the mass ratio of the two raw materials, and production optimization of the charge ratio is performed.

[0223] The materials were added in a mass ratio of ε-poly-L-lysine hydrochloride to sodium γ-polyglutamate of 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, and 1:5, respectively, and mixed at pH 7. The coacervate was separated and the SFA yield of each preparation example was determined based on the mass of the coacervate and the mass of the raw materials. The statistical graph of the SFA yield under each charge ratio is shown in FIG. Figure 1 As shown, it can be seen that the yield of SFA is the highest when the charge ratio of ε-poly-L-lysine hydrochloride and γ-polyglutamate is 1:1.

[0224] Next, at a charge ratio of 1:1 (equivalent to a feed mass ratio of 1:1), we studied the pH value of the mixture of ε-poly-L-lysine hydrochloride and γ-polyglutamate sodium solution. The pH was controlled by increasing the hydrochloric acid concentration or increasing the sodium hydroxide concentration. The pH was controlled at 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12, respectively. The coacervate was separated and the SFA yield of each preparation example was determined based on the mass of the coacervate and the feed mass. The SFA yield at each pH value is shown in Figure 2. Figure 2 As shown, the yield is higher at pH 2-10, preferably pH 4-8, at which the yield is about 80%, and the yield is highest at pH 7.

[0225] In principle, coacervate formation is less than 20% within the pH range of 11 to 12. This is likely due to the isoelectric points of the ε-poly-L-lysine hydrochloride units (~9.37) or the γ-polysodium glutamate units (~3.6), which are both within this range. We believe that under acidic conditions, the coexistence of charges of opposite polarity increases the likelihood of molecular entanglement to form electrocomplexes. The large number of charges of opposite polarity promotes this process. Therefore, mixing equal weights within the pH range of 4-8 is the optimal production method.

[0226] According to the above principle, pH not only affects the yield of SFA, but also affects the molecular entanglement structure of SFA at the microscopic level, thereby affecting the stability and adhesion performance of SFA. The pH was controlled to 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12, respectively, and the coacervate layer was separated. The shear modulus of the adhesive prepared at different pH values and the ceramic bonding was measured by referring to the method of Example 13. The results are shown in Table 7.

[0227] Table 7: Shear modulus of adhesives with different compositions before and after drying and ceramics

[0228]

[0229]

[0230] The above test results show that the adhesive properties of adhesives prepared at different pH levels vary. At pH 7, the shear modulus of the adhesive bonded to ceramics is the highest, and the tensile strength and lap strength follow the same trend as the shear modulus. Therefore, it can be considered that this is the best bonding performance. Secondly, the adhesive prepared at pH 4-8 exhibits higher adhesive properties. When the pH is less than 2 or greater than 10, the shear modulus of the adhesive decreases significantly, and the increase in shear modulus before and after drying decreases. The test results for bond strength are consistent with those for yield, and the principle behind the pH effect is the same: pH affects the microscopic molecular entanglement structure of SFA.

[0231] Example 31: Experiment on raw material concentration

[0232] SFA resembles snail mucus, exhibiting viscous but plastically deformable properties. While maintaining the same feed ratio that yielded the highest SFA yield, it is noteworthy that variations in the polymer salt solution feed concentration resulted in different viscosities and adhesion capabilities.

[0233] Solutions of ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate at different concentrations (5%, 10%, 15%, and 20%) were prepared and mixed at these concentrations to prepare SFA. The coacervates were separated, and the water content was calculated using the fresh and oven-dried masses. Rheological tests were performed on a TA Discovery HR-20 rheometer using parallel-plate geometry (20 mm diameter), a constant strain of 3%, a constant angular frequency of 10 rad / s, and a gap of 500 μm. The storage modulus (G'), loss modulus (G''), and complex viscosity (η) of the samples were recorded.

[0234] The higher the complex viscosity, the thicker the SFA formed. The higher the complex viscosity after drying, the higher the bonding strength of the SFA. In the wet state, the loss modulus of SFA is always greater than the storage modulus. The wetness of the SFA can be judged by the relationship between the two. The higher the storage modulus and loss modulus, the greater the bonding strength of the SFA.

[0235] The complex viscosity and water content of SFA at different mixing concentrations (i.e., the concentration of polymer aqueous solution) are as follows: Figure 3 As shown in Figure 3, when the concentration increases from 5% to 20%, the water content in SFA changes slightly from 62% to 64%. However, the complex viscosity (η) of SFA decreases sharply from 5% (337.9 Pa·s) to 20% (7.7 Pa·s), a decrease of nearly 44 times.

[0236] In addition, under constant stress, the loss modulus (G″) and storage modulus (G′) of SFA with different concentrations showed similar trends, e.g. Figure 4After evaporation-induced dehydration, lap shear tests on SFA-bonded glass slides revealed that, consistent with G′, G″, and η, the SFA formed at 5% had the strongest bond strength (4.08 MPa), far exceeding that of the SFA formed at 20% (1.57 MPa).

[0237] The mechanism behind this may be that increasing the raw material concentration compromises the molecular interactions between ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate due to increased steric hindrance, thereby reducing structural changes such as macromolecular polymer orientation or alignment and altering the viscoelastic behavior of the coacervate. During dehydration, the coacervate is further compressed into tightly entangled aggregates. The differential evolution of the secondary structure within the coacervate may influence the overall mechanical properties of the final aggregate, impacting its adhesion capacity.

[0238] In the field of hydrogels, hydrogels are often prepared using extremely low concentrations of positively charged polyamino acids and negatively charged polyamino acids, such as a concentration of 0.05%. At this concentration, molecular interactions between charged polyamino acids are difficult to fully occur, and no structural changes such as the arrangement of macromolecular polymers occur. The secondary structure of macromolecular polymers does not change. In addition, the raw material for hydrogel preparation is polyamino acids, not in the form of salt, so it does not have the properties of a snail-type adhesive.

[0239] The raw material concentration used in the present invention is much higher than the concentration used in hydrogel preparation, and the increase in concentration achieves unexpected results, achieving an effect similar to that of snail mucus. The adhesive properties are significantly increased after drying, and the adhesive effect on rough surfaces is even higher. However, the higher the concentration, the better. When the concentration increases, the adhesive properties decrease significantly. Therefore, preparation at a concentration of 5% is a necessary condition for achieving the best adhesive effect, which is also a major discovery of the present invention that breaks the prejudice of the prior art.

[0240] Example 32: Study on the bonding mechanism of adhesive

[0241] We have found that the snail-shaped adhesive of the present invention has significantly improved adhesive properties after drying, and its adhesive properties vary when applied to surfaces of different materials, with the highest adhesive properties being with ceramics. This example continues to study this conclusion.

[0242] The morphology and energy spectrum (EDS) of the samples were characterized by scanning electron microscopy (SEM) (Hitachi, SU5000). The same amount of ε-poly-L-lysine hydrochloride, γ-polyglutamate, SFA were distributed on the ceramic surface and then dried in an oven for 24 hours before observation. The glass samples glued by SFA were dried and cut to observe their cross sections using SEM (EM-30+, COXEM). Before SEM analysis, all samples were coated with a 10nm gold layer.

[0243] Scanning electron microscopy (SEM) images of ε-poly-L-lysine hydrochloride, γ-polyglutamate, and SFA dried on equal amounts of ceramics are shown in Figure 2. Figure 5 As shown in Figure 2, the two polyamino acid salt solutions showed a preference for penetrating and diffusing into the interior of the porous ceramics, while SFA formed a dense colloidal layer on the ceramic surface, showing strong interconnectivity. Further electron microscopy images of the dense colloidal layer of SFA on the ceramic surface are shown in Figure 2. Figure 6 shown.

[0244] Next, energy dispersive spectroscopy (EDS) was used to identify the dried raw materials and SFA, and the EDS module in a scanning electron microscope (Hitachi, SU5000) was used to perform elemental distribution identification on the dried raw materials and SFA. Figure 7 As shown in Figure 2, the Cl and Na contents in SFA are lower than the expected theoretical values (the average values of ε-poly-L-lysine hydrochloride and γ-polyglutamate sodium). The element distribution statistics of ε-poly-L-lysine hydrochloride, γ-polyglutamate sodium and their coacervates are shown in Figure 2. Figure 8 The significant reduction in Cl and Na content in SFA relative to ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate may result from the selective enrichment of Cl in the SFA phase during mixing. These findings provide a possible mechanism for the formation of SFA, which may involve liquid-liquid phase separation.

[0245] Optical microscope images verify the physical state of SFA, such as Figure 9 As shown in the figure, no matter it is a solid precipitate or a liquid coacervate, as the concentration of ε-poly-L-lysine hydrochloride and γ-polyglutamate sodium increases (0.05%, 0.5%, 5%), the droplets merge and eventually form an adhesive, indicating that SFA is formed through the liquid coacervate.

[0246] In addition, the huge viscosity (shear and tensile strength) is also caused by, for example Figure 10 The mechanism demonstrated is that at the microscopic level, the snail-type adhesive of the present invention can generate a huge hydrogen bonding force, and can produce a mechanical interlocking effect especially on the rough material surface.

[0247] CD spectroscopy (circular dichroism) is primarily used to determine the three-dimensional structure of proteins. Circular dichroism (CD) is the phenomenon of different absorption levels of R and L circularly polarized light. The relationship between this difference in absorption and wavelength is called CD spectroscopy, a spectroscopic method for determining asymmetric molecular structure. In molecular biology, it is primarily used to determine the three-dimensional structure of proteins, but can also be used to determine the three-dimensional structure of nucleic acids and polysaccharides. Aqueous solutions of coacervates and raw materials diluted to a concentration of 0.04 mg / mL were scanned using a BRIGHTTIME Chirascan (JASCO 810) to obtain raw CD spectral data in the wavelength range of 190 nm to 250 nm. This raw data was input into the open-source software BESTSEL for typing, which can determine the secondary structure and percentage of the macromolecule.

[0248] Infrared spectroscopy is a technique that uses the selective absorption of certain wavelengths of infrared light by molecules, which triggers transitions in their vibrational and rotational energy levels. This absorption can be used to determine the infrared absorption spectrum of a substance, also known as molecular vibrational spectroscopy (FTIR spectroscopy) or rotational-vibrational spectroscopy. ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate were dissolved in deuterated water (D2O) and centrifuged to form a coacervate. This method reduces the interference of hydrogen in the aqueous solution on the results. The raw data from the raw material and the coacervate were obtained using a Fourier transform infrared spectrometer (Vertex 70, Bruker, Germany), and the final FTIR spectrum was obtained after normalization.

[0249] The complex process of coacervate formation was characterized by secondary structure. The circular dichroism of coacervate, ε-poly-L-lysine hydrochloride and γ-polyglutamate sodium was shown in Figure 2. Figure 11 The percentage of secondary structures in coacervates, ε-poly-L-lysine hydrochloride, and γ-polyglutamate is shown in Figure 12 As shown, the CD spectrum of the coacervate is Figure 13 As shown, it is shown that ε-poly-L-lysine hydrochloride regulates the structure of γ-polyglutamate in aqueous solution by increasing the number of β turns and β sheets while reducing random curling. The FTIR spectrum of γ-polyglutamate is at 1592 and 1623 cm -1 The amide absorption peak at 1659 cm-1 of ε-poly-L-lysine hydrochloride in D2O is significant. -1 The characteristic amide absorption peak is shown at , and in the FTIR spectrum of the coacervate, the red shift of the amide I mode in the two macromolecular polymers indicates that the secondary structure of the macromolecular polymers has changed.

[0250] X-ray photon spectroscopy (XPS) is a technique for analyzing the surface chemical properties of materials. XPS can measure the elemental composition, empirical formula, elemental chemical state, and electronic state of materials. A beam of X-rays is used to excite the solid surface, and the kinetic energy of the electrons emitted within 1-10 nm of the surface of the analyzed material is measured to obtain the XPS spectrum. The photoelectron spectrum records electrons exceeding a certain kinetic energy. The peaks that appear in the photoelectron spectrum are the emission of electrons with certain characteristic energies in atoms. The energy and intensity of the photoelectron peaks can be used for qualitative and quantitative analysis of all surface elements. C1s is the photoelectron energy measured when the 1s orbital electrons in the carbon atom are excited. N1s is the photoelectron energy measured when the 1s orbital electrons in the nitrogen atom are excited. The dried ε-poly-L-lysine hydrochloride and γ-polyglutamate sodium and condensates were excited by an X-ray photon spectrometer (XPS, K-Alpha, Thermo Fisher Scientific, USA) to obtain a photon spectrum in the wavelength range of 500-4000 cm-1 with a resolution of 4.0 cm -1 .

[0251] The full XPS spectra of ε-poly-L-lysine hydrochloride, γ-polyglutamate and coacervate are as follows Figure 14 As shown, it shows that there is no new chemical bond in the mixture of the two components. The N1s spectra of ε-poly-L-lysine hydrochloride, γ-polyglutamate and coacervate are shown in Figure 15 As shown, a singularity is depicted at 399.4 eV, corresponding to the O=CN bond. In contrast, ε-poly-L-lysine hydrochloride and the coacervate exhibit two peaks, with a unique CNH peak at a binding energy of 401.2 eV. The peak area of CNH in ε-poly-L-lysine hydrochloride accounts for 40% of the total area, while in the coacervate, it is halved, indicating that ε-poly-L-lysine hydrochloride and γ-polyglutamate contribute significantly to the coacervate. The C1s spectra of ε-poly-L-lysine hydrochloride, γ-polyglutamate, and the coacervate are shown in Figure 1. Figure 16 The results show that the above conclusions are also confirmed. Therefore, the formation of coacervates mainly originates from physical interactions between macromolecular polymers, including hydrogen bonds and electrostatic forces. These physical interactions change the secondary structure of macromolecular polymers in solution and their physical properties, thereby inducing liquid-liquid phase separation.

[0252] Example 33: Comparison of snail-type adhesive and existing adhesive

[0253] The performance of SFA in bonding ceramics, glass, wood and steel was compared with that of reported bio-based adhesives and water-based synthetic adhesives according to the method for measuring lap strength in Example 13. The results are as follows: Figure 17 The bio-based adhesives and water-based synthetic adhesives reported include the adhesives reported in the following documents:

[0254]

[0255]

[0256] The results showed that SFA had slightly better bonding performance than previously reported bio-based adhesives for glass and wood, but was inferior to existing adhesives for steel. However, for ceramics, the adhesive's average lap shear bond strength of 27.8 MPa was higher than any other reported bio-based adhesive and even double that of a reported cyanoacrylate-based superglue (~13 MPa). Furthermore, tensile strength tests showed similar bonding performance.

[0257] The existing adhesives lack those with high adhesive properties to ceramics. The adhesive provided by the present invention provides an effective adhesive option to fill the gap in the field of ceramic adhesives.

[0258] Example 34: Broad Spectrum Durability of SFA

[0259] Ensuring the durability of the bond is a key factor in the long-term preservation and functionality of the bonded components. Based on the ASTM F1980-07 guideline, we used a standard accelerated aging technique, which is based on the assumption that the chemical reactions of the material during aging follow Arrhenius reaction kinetics. Specifically, the chemical reaction rate roughly doubled with a processing temperature increase of only 10°C. Accelerated aging tests were conducted under high temperature conditions (20% RH and 65°C, with temperature and humidity controlled by an accelerated aging chamber), and the bond strength of the bonded components was evaluated every 15 days for 75 days. Based on previously reported methods, the expected lifetime (RTY) was determined to be 16 times faster than the accelerated aging time (AAT).

[0260] The SFA obtained in Example 12 was used as the test product. The load-displacement curves of the SFA at different time points (0, 15, 30, 45, 60, and 75 days) in the accelerated aging test were as follows: Figure 18 As mentioned above, the lap strength of SFA is as follows Figure 19 As shown, the results show that there is no significant change in shear strength and lap strength during the entire testing period, indicating that the SFA bonded devices have the resilience to last for at least 3 years in a relatively arid environment.

[0261] In some special cases, such as use in spacecraft, adhesives need to withstand extreme temperature tests. On the sunlit side of the Earth, the temperature of a spacecraft or space station can exceed 100°C, while passing through the Earth's shadow at night, the temperature can drop to -100°C within 45 minutes. To address this issue, we conduct lap shear tests on the bonded ceramics at 100, 200, 300, and 400°C after controlled high temperature exposure in a muffle furnace for 30 minutes.

[0262] The SFA obtained in Example 12 was used as the test product. The load-displacement curves of the SFA after heating at different temperatures (25, 100, 200, 300, 400°C) for 30 minutes were as follows: Figure 20 As shown in Figure 2, the shear strength of SFA is Figure 21 As shown, the bio-based SFA adhesive showed no change in appearance and no loss of shear strength at both 100°C and 200°C, whereas the existing cyanoacrylate adhesive lost its adhesiveness at 200°C. At 300°C, the SFA carbonized. Although reduced to 22% of its initial value, the shear strength still exceeded 6 MPa. At 400°C, cohesive failure was observed in the SFA-bonded ceramic, which was attributed to the breakdown of intermolecular interactions. However, remnants of the SFA remained adhered to the ceramic surface, indicating a potential mechanical interlock between the adhesive and the surface.

[0263] DMA stands for dynamic mechanical analysis. Its testing principle is based on the change in elastic modulus under different mechanical conditions. During the test, the test sample is heated according to a program while a periodic oscillating force is applied to determine the elastic modulus and test certain characteristic points of the material. The SFA-bonded ceramic material is fixed in a dynamic mechanical analyzer (DMA) and cooled to -150°C using programmed liquid nitrogen. After the temperature is set, tension is applied to both ends of the ceramic sample and the shear stress is measured.

[0264] The adhesion of SFA at low temperature was tested by dynamic mechanical analysis (DMA), e.g. Figure 22 As shown in Figure 2, lap shear tests were performed on bonded ceramics under liquid nitrogen spray at -150°C for 30 minutes. Despite the inherent mechanical limitations of DMA, the samples maintained structural integrity during the test. Finally, we re-evaluated the low-temperature tolerance of SFA by testing them after immersion in liquid nitrogen. The results are shown in Figure 2. Figure 23 As shown, the tiles fractured before SFA, demonstrating their excellent low-temperature durability.

[0265] Example 35: Recyclability of SFA

[0266] Due to the physically cross-linked nature of coacervate-based adhesives, SFAs offer the advantage of reusability. Cracked areas can be effectively re-pressurized and cured after evaporation.

[0267] The SFA-bonded ceramic was subjected to 10 fracture-curing cycles, and a load test was performed each time using the same method as in Example 13. The load-displacement curves for the 10 fracture-curing cycles are shown in FIG. Figure 24As shown, lap shear tests recorded after each cycle show that repeated use of SFA does not reduce its bond strength, a feature that highlights its remarkable recyclability, surpassing traditional solvent-based adhesives and significantly contributing to reduced material consumption.

[0268] Furthermore, the non-covalent nature of the coacervate imparts additional useful features to SFAs, allowing for easier material separation and recovery after application. Separation of SFAs from substrates can be achieved by applying water or a moderately alkaline solution (pH < 10), such as water or sodium carbonate solution, under sufficient external peeling force, e.g. Figure 25 As shown, SFA can be separated from the slide by washing with sodium carbonate solution for 30 seconds. However, when the alkalinity of the solution exceeds a pH of 10, the yield of SFA decreases sharply, similar to the yield results in the preparation example above, because the alkaline solution disrupts the interaction between ε-poly-L-lysine hydrochloride and sodium γ-polyglutamate. However, when SFA is separated with water, it can be reused with the same viscosity as the original.

[0269] Therefore, the present invention also provides a convenient method for removing unwanted adhesives. This reversibility reduces pressure on landfills, reduces demand on limited resources, and promotes sustainability. Notably, the SFA's simple adhesive remover does not contain toxic solvents such as propane, acetone, and fluoride. These advantages suggest that our snail-inspired SFA has the potential to become an environmentally friendly alternative to existing solvent-based adhesives.

[0270] Example 36: Application of SFA

[0271] The extraordinary adhesive properties of SFA make it a valuable asset in all aspects of daily life.

[0272] Compared with previously reported bio-based and synthetic water-based adhesives, SFA exhibits very strong adhesive properties. For example, when the SFA prepared in Example 12 effectively adhered three ceramic sheets with an overlap of 3 cm, 2 , in shear tests under tension, it was able to support the weight of an adult weighing 75 kg, and even when the overlapping area was halved in the tensile test, the SFA showed excellent load-bearing capacity, e.g. Figure 26 Therefore, SFA can be used as an adhesive for load-bearing applications.

[0273] In addition to its wide range of applications, SFA is particularly useful in specialized settings, such as the restoration of archaeological artifacts. The strong adhesion of SFA to ceramics makes it suitable for repairing ceramic artifacts. Notably, the adhesion ability of SFA is not limited to porcelain, but also includes materials such as cattle bones, which have many micropores. For example, in an adhesion test, when a 20 kg bucket of water was lifted, a broken cattle femur sealed with SFA prepared in Example 12 remained intact, as shown in Figure 1. Figure 27 This suggests that SFA is promising for a wide range of applications, especially in establishing strong adhesion between objects with rough surfaces.

[0274] In addition, the recyclability of SFA enables SFA to be used as a reusable or green adhesive; the broad-spectrum durability of SFA enables SFA to be used as an adhesive in extreme temperature applications, such as in the aerospace field.

[0275] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined by the claims.

Claims

1. An adhesive, characterized in that It includes a viscous polymer formed by mixing a positively charged polymer salt solution and a negatively charged polymer salt solution.

2. The adhesive according to claim 1, wherein The polymer salt is a salt of a polymer having a degree of polymerization greater than 2.

3. The adhesive according to claim 1, wherein The positively charged polymer salt and the negatively charged polymer salt are water-soluble.

4. The adhesive according to claim 1, wherein The polymer salts are salts of naturally occurring polymers.

5. The adhesive according to claim 1, wherein The positively charged polymer salt solution includes any one or more of a positively charged amino acid polymer salt solution, a chitosan salt solution, and a polypropylamine salt solution; the negatively charged polymer salt solution includes any one or more of a negatively charged amino acid polymer salt solution, a hyaluronate solution, a chondroitin sulfate salt solution, and a polyacrylate solution.

6. The adhesive according to claim 5, wherein The positively charged polymer salt solution is a positively charged amino acid polymer salt solution; the negatively charged polymer salt solution is a negatively charged amino acid polymer salt solution.

7. The adhesive according to claim 6, wherein The positively charged amino acid polymer salt includes any one or more salts of polylysine, polyarginine, and polyhistidine; the negatively charged amino acid polymer salt includes any one or more salts of polyglutamic acid, polyaspartic acid, polyglycine, polyalanine, and polyvaline.

8. The adhesive according to claim 7, wherein The positively charged amino acid polymer salt is a salt of polylysine; the negatively charged amino acid polymer salt is a salt of polyglutamic acid.

9. The adhesive according to claim 8, wherein The positively charged amino acid polymer salt is ε-poly-L-lysine hydrochloride, and the negatively charged amino acid polymer salt is sodium gamma-polyglutamate.

10. The adhesive according to claim 6, wherein The positively charged amino acid polymer salt and / or the negatively charged amino acid polymer salt are salts of amino acid copolymers.

11. The adhesive according to claim 10, wherein The number of positively charged amino acid monomers in the amino acid copolymer of the positively charged amino acid polymer salt is greater than the number of negatively charged amino acid monomers, and / or the number of positively charged amino acid monomers in the amino acid copolymer of the negatively charged amino acid polymer salt is less than the number of negatively charged amino acid monomers.

12. The adhesive according to claim 1, wherein The pH of the positively charged polymer salt solution and the negatively charged polymer salt solution is 2-10.

13. The adhesive according to claim 12, wherein The pH of the positively charged polymer salt solution and the negatively charged polymer salt solution is 4-8.

14. The adhesive according to claim 13, wherein The pH of the positively charged polymer salt solution and the negatively charged polymer salt solution is 7.

15. The adhesive according to claim 1, wherein The charge ratio of the positively charged polymer salt solution to the negatively charged polymer salt solution is 1:0.2 to 1:

5.

16. The adhesive according to claim 15, wherein The charge ratio of the positively charged polymer salt solution to the negatively charged polymer salt solution is 1:

1.

17. The adhesive according to claim 1, wherein The concentrations of the positively charged polymer salt solution and the negatively charged polymer salt solution are 5-20%.

18. The adhesive according to claim 17, wherein The concentration of the positively charged polymer salt solution and the negatively charged polymer salt solution is 5%.

19. A method for preparing an adhesive, characterized in that: The following steps are involved: (1) Using a neutral buffer as a solvent, a positively charged polymer salt solution and a negatively charged polymer salt solution are prepared respectively; (2) The positively charged polymer salt solution and the negatively charged polymer salt solution are mixed and settled; (3) Separate the lower coacervate layer.

20. The preparation method according to claim 19, wherein Step (3) is: centrifugation to separate the lower coacervate layer.

21. A method for reusing an adhesive, characterized in that: After the test pieces are bonded with the adhesive according to any one of claims 1 to 18, they are immersed in water to separate them and then can be bonded again.

22. The method according to claim 21, wherein The pH of the sodium carbonate solution is less than or equal to 10.

23. Use of a mixture for preparing a reusable adhesive having improved bonding strength to a rough surface of a medium, characterized in that: The mixture includes a positively charged polymer salt solution and a negatively charged polymer salt solution.